Beginning tennis - Jensen, Julie, 1957-; King, Andy; Miller, Marc. (Minneapolis : Lerner Publications Co., 1995)
Gives basic techniques for playing tennis.
Second printing, 1998, contains updated information.
Includes bibliographical references (p. [62]) and index.
Wilson's Children.
4.2
3-6
Keywords: Tennis -- Juvenile literature; Tennis; Tennis